Spatial Analysis of Carbon Monoxide Factors on the Prevalence of Low-Birth-Weight Infants in the City of Palembang - Zalzabila, Anisah; Septiawati, Dwi; Ardillah, Yustini; Razak, Rahmatillah (Indonesian Journal of Global Health Research, 2024)
Carbon monoxide (CO) exposure has been linked to various health problems, including the risk of low birth weight (LBW) in newborns. Geographic Information Systems (GIS) in the health sector can be a way to collect information to manage health and environmental problems in regional-based environmental management. This study aims to analyze spatially the relationship between ambient CO concentrations and the prevalence of LBW in Palembang. This study used a quantitative approach with an ecological study design. CO concentration data were obtained from the Environmental Agency of Palembang City, while LBW prevalence data were obtained from the Health Office of Palembang City. Spatial and time-series analyses were conducted to examine the serial relationship between pollutant concentration time series data and LBW occurrence time series data during the period of 2019 – 2023. In the 2019-2022 period, the CO concentrations in the city of Palembang showed fluctuating results in each district. The lowest CO concentration was recorded in 2020 at 1984 µg/Nm³/hour and the highest was in 2022 at 13568 µg/Nm3/hour. The highest number of LBW cases was 58 babies in 2023, and consistently zero case during the period of 2020-2023 in one district. There is a relationship between CO concentrations in 2021-2022 and LBW occurrences in 2022-2023 in Ilir Timur I district. However, when viewed over a longer period, there is no relationship between the average CO concentration from 2019-2022 and the average LBW prevalence from 2020-2023 in the city of Palembang.